Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan, Pertumbuhan Perusahaan, PER dan Struktur Modal Terhadap Nilai Perusahaan - Kezia Meilani Bororing; Muhammad Rifki Bakhtiar (Universitas Muhammadiyah Metro, 2025)
The main goal of the company is to improve the company's performance in order to make its shareholders prosperous. The level of success of company management can be measured by the value of a company. This research aims to determine the effect of Profitability, Leverage, Company Size, Company Growth, Price Earning Ratio and Capital Structure on Company Value. The object of this research is food and beverage companies registered on the IDX in 2018-2022. The population in this study was 26 companies. The sampling technique is using a purposive sampling method with a sample of 14 companies. This research is quantitative research. This research uses descriptive statistical analysis, classical assumption testing, multiple linear regression analysis and hypothesis testing. Data processing uses SPSS Version 22. Based on the results of the research that has been conducted, it can be concluded that Profitability, Leverage, Company Size, and Price Earning Ratio have a positive effect on Company Value, while Company Growth has a negative effect on Company Value, and Capital Structure has no effect on Company Value.